Applications of Control Theory to Economic Analysis / Contributions to Economic - Pitchford John D; Turnovsky Stephen J (North Holland Publishing Company, 1977)
Preface, Non-Linear Models - Introduction, Optimal Control Theorems, Resource Depletion with Possible Non-Convexities in Production, Otimal Exploitation and Replenishment of a Natural Resource, The Adjustment Cost Problem with Jumps in the State Variable, Two State Variable Problems, Linear Stablilisation Models, Policy Objectives and Instrument Requirements for a Dynamic Theory of Policy, Existence and Uniqueness and Stability of Linear Optimal Stabilisation Policies, Optimal Control of Linear Systems with Stochastic Coefficients and Additive Disturbances, On the Scope of Optimal and Discretionary Policies in the Stabilisation of Stochastic linear Systems.